Pengaruh Beban Kerja dan Kepuasan Kerja Terhadap Kinerja Perawat di Ruang Rawat Inap Rumah Sakit Umum Haji Medan - Gusti Ramida Pasaribu; Agus Rahmadsyah (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This study aims to determine the effect of workload and job satisfaction on performance in the inpatient room at Haji General Hospital, Medan. The population in this study was 132 nurses, with a total sample of 70 people taken, namely all civil servant nurses in the inpatient room. The data analysis used is path analysis. Research data was collected using a questionnaire. With Cronbach alpha reliability, workload is 0.867, job satisfaction is 0.856, and performance is 0.826. The research results show that: (1) There is a positive and significant influence between workload on nurse performance; (2) There is a positive and significant influence between job satisfaction and nurse performance; (3) There is a positive and significant influence between workload and job satisfaction on nurse performance.